Anisodamine Maintains the Stability of Intervertebral Disc Tissue by Inhibiting the Senescence of Nucleus Pulposus Cells and Degradation of Extracellular Matrix via Interleukin-6/Janus Kinases/Signal Transducer and Activator of Transcription 3 Pathway - Tang, Ning; Dong, Yulei; Chen, Chong; Zhao, Hong (Frontiers in Pharmacology, 2020)
Objective: Anisodamine (ANI) has been used to treat a variety of diseases. However, the study of ANI in intervertebral disc degeneration (IVDD) is unclear. This study investigated the effects of ANI on degenerative nucleus pulposus cells (NPCs) and IVDD rats, and its possible mechanisms. Methods: Human nucleus pulposus cells (HNPCs) were treated with IL-1β (20 ng/mL) to simulate IVDD, and an IVDD rat model was constructed. IL-1β-induced HNPCs were treated with different concentrations (10, 20 or 40 μM) of ANI, and IVDD rats were also treated with ANI (1 mg/kg). Results: ANI treatment significantly reduced the apoptosis, caspase-3 and SA-β-gal activities, and p53 and p21 proteins expression, while promoted telomerase activity and aggrecan and collagen II synthesis in IL-1β-induced HNPCs. Moreover, the introduction of ANI inhibited the expression of IL-6, phosphorylation of JAK and STAT3, and nuclear translocation of p-STAT3 in Degenerated HNPCs. Additionally, the application of ANI abolished the effects of IL-6 on apoptosis, SA-β-gal and telomerase activity, and the expression of p53, p21, aggrecan and collagen II proteins in degenerated HNPCs. Simultaneously, ANI treatment enhanced the effects of AG490 (inhibitor of JAK/STAT3 pathway) on IL-1β-induced apoptosis, senescence and ECM degradation in HNPCs. Furthermore, ANI treatment markedly inhibited the apoptosis and senescence in the nucleus pulposus of IVDD rats, while promoted the synthesis of aggrecan and collagen II. ANI treatment obviously inhibited JAK and STAT3 phosphorylation and inhibited nuclear translocation of p-STAT3 in IVDD rats. Conclusion: ANI inhibited the senescence and ECM degradation of NPCs by regulating the IL-6/JAK/STAT3 pathway to improve the function of NPCs in IVDD, which may provide new ideas for the treatment of IVDD.